MOTIVASI ALUMNI SMKN 1 BANDAR SEI KIJANG DALAM MEMILIH BEKERJA ATAU MELANJUTKAN STUDI - Arniwati "; Swis Tantoro (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
The aim of This research is to know what are main cause of alumni of SMKN 1Bandar Sei Kijang who didn’t have work and continue their studies with the good conditions and better in econimoc, how much is the effect and motivation from themselves. The methodology of this research is descriptive qualitative and the technique of collecting data is pupisive the criteria of the informan is: the alumni of SMKN1 Bandar Sei Kijang from 2013 to 2015, don’t have job and don’t continue their studies. The results of this research are because the inaduquate saleries, their pay cuts due to negligence, the motivation of alumni to continue the studies is low, and the perception of work is better than continue the studies.Keywords : Motivation, Work, Proceedings Studies